Ethylene Telomerization Reaction with Alcohols Chromatographic Mass Spectrometry Analysis of The Product - Khudayberganova Sevara Zokirjonovna (Scientific Trends, 2024)
Scientific research is being conducted worldwide to improve the quality of substances synthesized through the processing of oil and natural gas, create new technologies that meet environmental requirements, and modernize existing technologies. Nowadays, it is of significant importance to develop new and efficient methods for the production of various chemicals using oil and gas products, as well as secondary raw materials obtained from their processing, and to create modern equipment for these processes.
Keywords: Ethylene, methanol, acetone, radical, telomer, telogen.